Vulnerabilidade ecoturística no Caminho dos Diamantes - Estrada Real/MG - Barbosa, Flávia Machado da Cruz Pinheiro; Castro, José Flávio Morais (Caderno de Geografia, 2009)
O Caminho dos Diamantes que integra a Estrada Real/MG propicia o desenvolvimento de várias modalidades ecoturísticas pela diversidade de atrativos naturais. o principal objetivo desta pesquisa é fornecer subsídios técnico-metodológicos ao planejamento Ecológico-econômico do Estado de Minas Gerais - ZEE-MG, que permitiram a realização da análise espacial dos recursos ecoturísticos, estreitando relações entre a Geografia e o Turismo. O resultado final é o mapa de vulnerabilidade ecoturística produzido por meio de técnicas de geoprocessamento e desenvolvido a partir das análises da potencialidade ecoturística da área de estudo e da vulnerabilidade natural. Abstract The Diamond Route that integrates the Royal Road, Minas Geais State, fosters the development of various forma of ecotourism for the diversity of its natural attractions. Tha main objetive of this research is to provide technical and methodological subsidies to ecotourism planning on the Diamond Route, based on results obtained from the Ecological and Economic Zoning of Minas Gerais State, which allowed the elaboration of a spatial analysis of ecotourism resources, emphasizing the connection between Geography and tourism. The final result is the map of ecotourism vulnerability designed with geoprocessing techniques and developed with basis on the analyses of ecotourism potentialities in the studied area, as well as natural vulnerability.